ISLAMIC EDUCATION LEADERSHIP GENDER PERSPECTIVE - Isti Isti; Taufik Adji Sasono (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Islamic Education Leadership Gender Perspective. Nowadays, there are many women who become leaders. In this case, many women have succeeded in reaching positions from low to high positions in an institution or state. In fact, history has recorded that several women are successful on the political and become a minister, vice president, president or prime minister. Many women even became chairman of the courts, at the district level, at the provincial and even central levels. This fact has caused polemics among Muslims, especially Ulama and Islamic organizations related to the Islamic view of the existence of women in strategic positions in the public sector. This polemic comes from the view of differences in the biological structure of men and women which have implications for their roles in society. The Islamic Leadership has major position to be considered and carried out as well as possible. The Islamic view of leadership must be held by people who are capable and can place themselves as carriers of truth by giving good role models, because leaders are uswatun hasanah (good role models). There are opinions that allow women to lead the state, there are also opinions that do not allow it. Each opinions is strengthened by the arguments that come from the Qur'an and hadith. The hadith that is a reference to the prohibition of becoming the leader of state for women is a hadith narrated by Abu Bakrah which means